Analisis Produktivtas Alat Berat Pada Proyek Pembangunan Jalan Akses dan Fasilitas Pendukung Stasiun Maros - Herby Calvin Pascal Tiyouw; Helen Adry Irene Sopacua; Alvone Feldian Sampe Kondoallo (Paulus Civil Engineering Journal, 2025)
Road construction as  access and connection to an area is beneficial, among other things,  to facilitate the mobilization of goods and services, improve the economy and connectivity between regions. The Maros district government is constructing a new road to connect Maros Train Station with the main road, with a length of 2.5 km. The work carried out is land leveling. This work uses heavy equipment to achieve high productivity so that the work can be completed on time, on budget, and with high quality. Four units of construction equipment were used according to their functions, including dump trucks to transport material from the quarry to the project site, excavators to spread the material, bulldozers to level it, and vibration rollers to compact it. Research was conducted to determine the productivity of each tool according to its function and characteristics.  The results of the research on the productivity of each tool showed that the productivity of the dump truck was 14.78 m3/hour, the excavator was 337.62 m3/hour, the bulldozer was 91.12 m3/hour, and the vibration roller was 110.67 m3/hour.